If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8c + -1c + -1 = 9 Reorder the terms: -1 + 8c + -1c = 9 Combine like terms: 8c + -1c = 7c -1 + 7c = 9 Solving -1 + 7c = 9 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 7c = 9 + 1 Combine like terms: -1 + 1 = 0 0 + 7c = 9 + 1 7c = 9 + 1 Combine like terms: 9 + 1 = 10 7c = 10 Divide each side by '7'. c = 1.428571429 Simplifying c = 1.428571429
| 3(24-x)=6-x | | 14c-11=3(2c+7) | | 7=3-2+4x | | 6(w-2)+3w=24 | | (A+b)+3= | | 25xsquared-16=0 | | 3a+45+2a-10=180 | | .75n-2=-.875n+32 | | 3X-16=2N+18 | | 11x+10x=12x | | 5sinx+4cosx=0 | | 8c-(c-1)=9 | | -5x^2+39x+8=0 | | -24=3v+4(v+8) | | 4y+y+1=7y | | 3x-8+x+26=180 | | 6x-5(x-7)=-10 | | -24=3v+4(4+8) | | -5(r+7)=-87 | | 50+3x=x+82 | | -2=7(x-6)-2x | | 3x-7=5x-45 | | 9+8(5x+3)=-3-5(8x+3) | | -8x+9=-8x+5 | | -3.5x^2+42t+13=0 | | -3(2x-3)=4(x-7) | | 4(6x+2)=8(3x+1) | | .03x+.12(20)=.06+20+x | | 0.03=0.01+2.9 | | x^2-14x=-46 | | 46+12x=17x | | 1.2+12.2= |